Application of Traditional Chinese Medicine in Treating COVID-19 - Meng-Cheng Liu; Hong-Yun Gao (Chinese Medicine and Culture)
Traditional Chinese medicine (TCM) has been applied to the treatment of the novel coronavirus (COVID-19). In the epidemic, COVID-19 patients were treated through integrated TCM and Western medicine. The effect was remarkable, especially in the treatment of mild COVID-19 cases. This paper introduces several TCM treatments to COVID-19, put forward by both domestic and foreign scholars.